Is the Discount Really Favorable? The Effect of Numeracy on Price Magnitude Judgment: Evidence From Electroencephalography - Huang, Bijuan; Liu, Xiaoyu; Wang, Yangyang; Li, Hongxia; Si, Jiwei; Wang, Dawei; Afzal, Komal (Frontiers in Neuroscience, 2022)
Attractive price promotion will induce an unreasonable willingness to purchase especially through shopping. However, it’s not clear how numeracy, one of the essential abilities for understanding and applying numbers, influences the process of purchase judgement. Using electroencephalography, 61 participants were recruited to perform a price promotion task. The results showed that consumers low in numeracy performed worse than their peers high in numeracy at the behavioural level, and they also had lower P3b amplitude and less alpha desynchronization regardless of price promotion frameworks. These findings provided evidence on the processing of price information and provided further insight into how numeracy impacts price magnitude judgement.